ANALISIS PERKEMBANGAN PARADIGMA CYBER NOTARY: SINTESIS ATAS PROBLEMATIKA PENGATURAN CYBER NOTARY DI INDONESIA - Ni Putu Kompiang Ratna Dewi; Anak Agung Ayu Intan Puspadewi (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2025)
This article aims to understand and analyze the development of the cyber notary paradigm in order to achieve a synthesis of the dialectical problems of cyber notary regulation in Indonesia. This scientific article is normative legal research that uses a statutory approach and a conceptual approach. This research shows that the bias in understanding cyber notaries paradigm in Indonesia which emphasizes modernization of the implementation of notary authority has resulted in the regulation regarding cyber notaries to this day still standing in place. So, it is necessary to separate the concept of the cyber notary as a way to provide legal certainty and protection in electronic transactions by modernizing the implementation of notary authority by utilizing technology. The modernization of the implementation of the notary's authority should be studied carefully so as not to deny the basic principles of the implementation of the notary's authority. While the implementation of the cyber notary as providing legal certainty and protection in electronic transactions should focus on reviewing and regulating the types of electronic transactions, the relevance of the notary's office area, notary legal instruments/products, the strength of evidence and dispute settlement procedures as well as the special expertise that a notary must have to support the implementation of cyber notaries.